Activation of cardiac macrophages, endothelial cells and fibroblasts in experimental autoimmune myocarditis. (3rd October 2022) - Tkacz, K; Rolski, F; Jazwa-Kusior, A; Dzialo, E; Czepiel, M; Warszynska, M; Weglarczyk, K; Szatanek, R; Siedlar, M; Kania, G; Blyszczuk, P
Abstract: Background/Introduction: Inflammation of cardiac tissue, termed myocarditis, is a common cause of dilated cardiomyopathy associated with abnormal tissue remodeling, stiffening of ventricles and heart failure. Experimental autoimmune myocarditis (EAM) represents CD4+ T cell-dependent animal model of acute myocarditis followed by development of cardiomyopathy, cardiac fibrosis and systolic dysfunction. Purpose: The aim of the study was to investigate the role of cardiac macrophages, endothelial cells and fibroblasts in myocarditis and post-inflammatory cardiomyopathy in mouse model of EAM. Methods: EAM was induced in BALB/c mice by immunization with alpha myosin heavy chain and complete Freund's adjuvant. Reporter mice expressing EGFP under collagen type I promoter (Coll-EGFP), transgenic αSMA-TK mice with ganciclovir-inducible ablation of proliferating myofibroblasts and Rosa26-YFP/LysM-Cre and Rosa26-YFP/LysM-Cre/Tgfbr2 fl/fl with YFP expression and Tgfbr2 deletion in myeloid cell population were used in this study. Cardiac fibroblasts and macrophages were sorted using BD FACSAria™ II Cell Sorter and analyzed for the genome transcriptomics by RNA sequencing. Echocardiography was performed on Vevo 2100 Imaging System. Cardiac fibrosis was measured as percentage of fibrotic area using Trichrome Massons's staining and by hydroxyproline assay. Cardiac hypertrophy was analyzed as means of cross-sectional cardiomyocyte area. Monocytes and endobcells were analyzed using BD FACSCanto™ II flow cytometry. Results: Cardiac fibroblasts in response to acute myocarditis (d21 of EAM) showed activation of immune processes (mainly chemokine production such as Ccl6, Ccl9, Cxcl2, Cxcl3, Cxcl5, Cxcl9, Cxcl13), cytoskeletal re-organization (Cxadr, F11r, Gdpd2, Krt8, Krt19, Ptk2b, Rac2, Rhov, Rnd1, S100a9, Spire2, Was) and upregulation of genes involved in extracellular matrix turnover (Bmp7, Kng2, Lgals3, Cthrc1, Cela1, Spn) including collagens. Ablation of myofibroblasts (between d21–40 of EAM) resulted in markedly reduced heart weight and cardiomyocyte hypertrophy, attenuated expression of genes related to hypertrophy (Acta1, Actc1, Bnp, Cfl2, Pdlim5), improved stroke volume, ejection fraction and cardiac output but did not prevent development of post-inflammatory cardiac fibrosis measured at d40 of EAM. Analysis of monocytes and endothelial cells indicated excessive production of type I collagen by these cells at d21. Analysis of cardiac macrophages pointed out TGF-β-dependent expression of cytokines (Ifn, Il23a, Il10, Il12b, Cxcl1, Tnf) and theirs receptors (Cxcr1, Ccr4) at d21 of EAM. Conclusions: Acute myocarditis activates proinflammatory and profibrotic responses in cardiac resident cells. Our data suggest that cardiac myofibroblasts play a particularly important role in development of post-inflammatory cardiomyopathy and heart failure. Targeting cardiac myofibroblasts might therefore represent a novel therapeutic strategy in inflammatory heart disease. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre (Poland)